Survival outcomes and prognostic factors of lung cancer patients with the MET exon 14 skipping mutation: A single-center real-world study - Gow, Chien-Hung; Hsieh, Min-Shu; Chen, Yi-Lin; Liu, Yi-Nan; Wu, Shang-Gin; Shih, Jin-Yuan (Frontiers in Oncology, 2023)
Introduction: The MET exon 14 skipping (METex14) mutation is an important oncogenic driver in lung cancer. We performed a retrospective analysis of clinical data from lung cancer patients with the METex14 mutation to analyze their survival outcomes and associated prognostic factors. Methods: A one-step reverse transcription-polymerase chain reaction to examine the presence of the METex14 mutation was performed using RNA samples from 1374 lung cancer patients with no detected EGFR and ALK mutations. Pathological features and immunohistochemistry (IHC) results for c-MET were analyzed in patients with METex14-positive tumors. Results: METex14 was identified in 69 patients with lung cancer, including 53 adenocarcinoma (ADC) and 16 non-ADC patients. In comparison with patients without the METex14 mutation, lung cancer patients harboring the METex14 mutation were generally elderly individuals, never-smokers, and had poor performance scores. A higher frequency of METex14 mutations was detected in pulmonary sarcomatoid carcinoma (PSC) patients (24.3%, n = 9/37). However, stage IV PSC patients with or without the METex14 mutations showed similarly poor overall survival (OS) (p = 0.490). For all 36 METex14-positive lung ADCs, multivariate analysis showed several poor prognostic factors, including strong c-MET IHC staining (p = 0.006), initial brain metastasis (p = 0.005), and administration of only supportive care (p < 0.001). After excluding seven patients who received only supportive care, we further analyzed 29 stage IV lung ADC patients with METex14 mutations who received anti-cancer treatment. Multivariate analysis showed that pemetrexed treatment (p = 0.003), lung radiotherapy (p = 0.020), initial brain metastasis (p = 0.005), and strong c-MET IHC staining (p = 0.012) were independent prognostic factors for OS in these patients. Conclusions: A higher frequency of METex14 mutations was detected in PSC patients. Stage IV PSC patients with or without the METex14 mutations had similarly poor overall survival. Pemetrexed-based chemotherapy, strong c-MET ICH staining, initial brain metastasis, and lung radiotherapy, may help predict survival outcomes in patients with advanced lung ADCs harboring the METex14 mutation.